THE EFFECT OF PROFIT GROWTH, FIRM SIZE, AND LIQUIDITY OF EARNINGS QUALITY - Hairul Anam; Afrohah Afrohah (Jurnal Ekonomi dan Manajemen, 2020)
This study aimed to examine the effect of profit growth, firm size, and liquidity to the earnings quality. This study uses secondary data from the financial statements of pharmaceuticals published by Indonesia Stock Exchange during 2013 to 2017. Sampling technique by using purposive sampling. The sample in this study is pharmaceuticals company listed in Indonesia Stock Exchange as many as 7 companies. Method of data were analyzed by multiple linear regression. The result of partially test shows that profit growth and firm size had effect to earnings quality, and the liquidity had not effect to earnings quality. However, the result of simultaneously test show that profit growth, firm size, and liquidity had effect to earnings quality.